Resveratrol prevents hearing loss and a subregion specific- reduction of serotonin reuptake transporter induced by noise exposure in the central auditory system - Cheng, Long-Quan; Shu, Fang-Qi; Zhang, Min; Kai, Yuan-Zhong; Tang, Zheng-Quan (Frontiers in Neuroscience, 2023)
Prolonged or excessive exposure to noise can lead to hearing loss, tinnitus and hypersensitivity to sound. The effects of noise exposure on main excitatory and inhibitory neurotransmitter systems in auditory pathway have been extensively investigated. However, little is known about aberrant changes in neuromodulator systems caused by noise exposure. In the current study, we exposed 2-month-old mice to a narrow band noise at 116 dB SPL for 6 h or sham exposure, assessed auditory brainstem responses as well as examined the expression of serotonin reuptake transporter (SERT) in the cochlear nucleus (CN), inferior colliculus (IC), and primary auditory cortex (Au1) using immunohistochemistry. We found that noise exposure resulted in a significant increase in hearing thresholds at 4, 8, 16, 24, and 32 kHz, as well as led to a significant reduction of SERT in dorsal cochlear nucleus (DCN), dorsal IC (ICd), external IC (ICe), and Au1 layers I-IV. This reduction of SERT in these subregions of central auditory system was partially recovered 15 or 30 days after noise exposure. Furthermore, we examined efficacy of resveratrol (RSV) on hearing loss and loss of SERT induced by noise exposure. The results demonstrated that RSV treatment significantly attenuated threshold shifts of auditory brainstem responses and loss of SERT in DCN, ICd, ICe, and Au1 layers I-IV. These findings show that noise exposure can cause hearing loss and subregion-specific loss of SERT in the central auditory system, and RSV treatment could attenuate noise exposure-induced hearing loss and loss of SERT in central auditory system.